Terroir Is the Main Driver of the Epiphytic Bacterial and Fungal Communities of Mango Carposphere in Reunion Island - Taîbi, Ahmed; Rivallan, Ronan; Broussolle, Véronique; Pallet, Dominique; Lortal, Sylvie; Meile, Jean-Christophe; Constancias, Florentin (Frontiers in Microbiology, 2021)
The diversity of both bacterial and fungal communities associated with mango surface was explored using a metabarcoding approach targeting fungal ITS2 and bacterial 16S (V3-V4) genomic regions. Fruits were collected in Reunion Island from two different orchards according to a sampling method which allowed the effect of several pre-harvest factors such as geographical location (terroir), cultivars, fruit parts, tree position in the plot, fruit position on the tree (orientation and height), as well as the harvest date to be investigated. A total of 4,266,546 fungal and 2,049,919 bacterial reads were recovered then respectively assigned to 3,153 fungal and 24,087 to bacterial amplicon sequence variants (ASVs). Alpha and beta diversity, as well as differential abundance analyses revealed variations in both bacterial and fungal communities detected on mango surfaces depended upon the studied factor. Results indicated that Burkholderiaceae (58.8%), Enterobacteriaceae (5.2%), Pseudomonadaceae (4.8%), Sphingomonadaceae (4.1%), Beijerinckiaceae (3.5%), and Microbacteriaceae (3.1%) were the dominant bacterial families across all samples. The majority of fungal sequences were assigned to Mycosphaerellaceae (34.5%), Cladosporiaceae (23.21%), Aureobasidiaceae (13.09%), Pleosporaceae (6.92%), Trichosphaeriaceae (5.17%), and Microstromatales_fam_Incertae_sedis (4.67%). For each studied location, mango fruit from each cultivar shared a core microbiome, and fruits of the same cultivar harvested in two different locations shared about 80% fungal and bacterial family taxa. The various factors tested in this study affected bacterial and fungal taxa differently, suggesting that some taxa could act as geographical (terroir) markers and in some cases as cultivar fingerprints. The ranking of the factors investigated in the present study showed that in decreasing order of importance: the plot (terroir), cultivar, fruit parts, harvest date and the position of the fruits are respectively the most impacting factors of the microbial flora, when compared to the orientation and the fruit position (height) on the tree. Overall, these findings provided insights on both bacterial and fungal diversity associated with the mango surface, their patterns from intra-fruit scale to local scale and the potential parameters shaping the mango microbiota.